"Keeping the Boogie Man Away": Medication Self-Management among Women Receiving Anastrozole Therapy. (27th December 2012) - Wickersham, Karen; Happ, Mary Beth; Bender, Catherine M.
Abstract : The oral hormonal agent anastrozole improves clinical outcomes for women with breast cancer, but women have difficulty taking it for the five-year course. The unique medication-taking experiences related to self-management of anastrozole therapy for women with early stage breast cancer are not known. Our purpose was to describe the medication-taking experiences for postmenopausal women with early stage breast cancer who were prescribed a course of anastrozole therapy. Twelve women aged 58 to 67 years, midway through therapy, participated in audio-recorded interviews. Women's medication-taking experiences involved a belief in their importance and an imperative to take anastrozole. We found that women's side effect experiences, particularly menopausal symptoms, were significant, but only one woman stopped anastrozole due to side effects. Medication-taking included routinization interconnected with remembering/forgetting and a storage strategy. Some women noted a mutual medication-taking experience with their spouse, but most felt taking anastrozole was something they had to do alone. Our results provide insight into the way some women with early stage breast cancer manage their hormonal therapy at approximately the midpoint of treatment. Next steps should include examinations of patient-provider communication, potential medication-taking differences between pre- and postmenopausal women, and the effects of medication-taking on clinical outcomes.